1968
DOI: 10.1029/wr004i002p00273
|View full text |Cite
|
Sign up to set email alerts
|

United States tritium rainout and its hydrologie implications

Abstract: Tritium concentrations of precipitation, total rainout, and rainfall amounts for 1964 and 1965 are listed for 15 stations in the conterminous United States, Alaska, and Puerto Rico. These data show that the major increase in tritium rainout observed in 1963 was followed by • decline of about 27% in 1964 compared with 1963, and an additional decline of about 54% in 1965 compared with 1964. Rainout patterns are characterized by increases in tritium rainout with northern latitudes and with distance from the ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The tritium data are reported in picocuries per liter (pCi/L), a non-SI unit of radioactivity equivalent to 0.037 Becquerels per liter (Bq/L) or approximately 0.3125 TU (Stewart & Farnsworth, 1968 The water isotope data from the NGMS and LWIA were calculated by linear bestfit between the raw measurements and the known standards. The six values for each sample were then averaged.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The tritium data are reported in picocuries per liter (pCi/L), a non-SI unit of radioactivity equivalent to 0.037 Becquerels per liter (Bq/L) or approximately 0.3125 TU (Stewart & Farnsworth, 1968 The water isotope data from the NGMS and LWIA were calculated by linear bestfit between the raw measurements and the known standards. The six values for each sample were then averaged.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The authors found that tritium content in precipitation generally increased with latitude and was higher at inland than coastal sites, even though coastal areas had a greater amount of rain. Within California, tritium was shown to generally increase inland, especially to the northeast (Stewart & Farnsworth, 1968). (Stewart & Farnsworth, 1968).…”
Section: Introduction Tritiummentioning
confidence: 99%
See 1 more Smart Citation
“…As figure (Stewart and Farnsworth, 1968;Stewart and Wyerman, 1970). The line may therefore be taken to represent the approximate tritium content of shallow, recently recharged ground waters at these latitudes.…”
Section: Isotopesmentioning
confidence: 99%
“…Concentrations of tritium in water can be determined, but extensive concentration and highly sensitive detection procedures are required, because the tritium concentration in normal rainwater is only about 10 tritium atoms per 1018 normal hydrogen atoms. Stewart and Farnsworth (1968) presented detailed data on tritium in rainfall in the United States in the period 1963-65. The half life of tritium is 12.3 years, and it can, therefore, be used as a means of determining how long a particular water may have been stored out of contact with fresh supplies of tritium.…”
Section: Other Radioactive Nuclidesmentioning
confidence: 99%